UJI DISINTEGRASI DAN DISOLUSI TERBANDING TABLET ALOPURINOL GENERIK BERMEREK DAN GENERIK BERLOGO YANG BEREDAR DI PASARAN - Bambang Hernawan Nugroho; Yandi Syukri; Anik Ariyani (Jurnal Ilmiah Farmasi, 2009)
ABSTRACTAllopurinol is a pyrimidine derivative that effective to normalize levels of uric acid in bloodand urine. Allopurinol is very slightly soluble in water, but it has high permeability (BCS class II) sothat the dissolution is an important determine to express the drug bioavailability. Additional materialdifferences and the production process of each plant can cause differences in the quality of theresulting allopurinol tablets. This study aimed to compare the quality of branded generic andgeneric products allopurinol tablets in the quality of disintegration and dissolution. This study used 5kinds branded generic (A, B, C, D, E) and 5 kinds of generic products (F, G, H, I, J). Disintegrationtest carried out according to USP-NF 32ndedition by the medium of water at 37 ± 2°C. Dissolutiontests conducted according to USP-NF 32ndedition using apparatus 2 (paddle methode), the speedof rotation 75 rpm, in 0.01 N HCl medium at 37 ± 0.5°C. The data obtained compared with therequirements listed in the Indonesia Pharmacopoeia 4thedition and USP-NF 32ndedition, and thenstatistically analyzed by T test at 95% confidence interval. Results of disintegration and dissolutiontests met the requirements in the literature. Statistical test results showed that products haddifferent disintegration and dissolution profile.Keywords: allopurinol, disintegration, dissolution, tablets